Release characteristics of chitosan treated alginate beads: II. Sustained release of a low molecular drug from chitosan treated alginate beads - SEZER, ALİ DEMİR (My University, 1999)
The aim of this paper was to investigate the possible applicability of chitosan treated alginate beads as a controlled release system of small molecular drugs with high solubility. Timolol maleate (mw 432.49) was used as a model drug. The beads were prepared by the ionotropic gelation method and the effect of various factors (alginate, chitosan, drug and calcium chloride concentrations, the volume of external and internal phases and drying methods) on bead properties were also investigated. Spherical beads with 0.78-1.16 mm diameter range and 10.8-66.5% encapsulation efficiencies were produced. Higher encapsulation efficiencies and retarded drug release were obtained with chitosan treated alginate beads. Among the different factors investigated such as alginate, drug, chitosan and CaCl2 concentrations, the volumes of the external and internal phases affected bead properties. The drying technique has an importance on the bead properties also. The release data was kinetically evaluated. It appeared that chitosan treated alginate beads may be used for a potential controlled release system of small molecular drugs with high solubility, instead of alginate beads.
Keywords: Alginate; Beads; Chitosan; Controlled release; Timolol maleate